Electrochemical Study of Copper Ferrite as a Catalyst for CO2 Photoelectrochemical Reduction - Kaykobad Md. Rezaul Karim; Huei Ruey Ong; Hamidah Abdullah; Abu Yousuf; Chin Kui Cheng; Mohd. Maksudur Rahman Khan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
In this work, p-type CuFe2O4 was synthesized by sol gel method. The prepared CuFe2O4 was used as photocathode catalyst for photoelectrochemical (PEC) CO2 reduction. The XRD, UV-Visible Spectroscopy (UV-Vis), and Mott-Schottky (MS) experiments were done to characterize the catalyst. Linear sweep voltammetry (LSV) was employed to evaluate the visible light (λ>400 nm) effect of this catalyst for CO2 reduction. The band gap energy of the catalyst was calculated from the UV-Vis and was found 1.30 eV. Flat band potential of the prepared CuFe2O4 was also calculated and found 0.27 V versus Ag/AgCl. Under light irradiation in the CO2-saturated NaHCO3 solution, a remarkable current development associated with CO2 reduction was found during LSV for the prepared electrode from onset potential -0.89 V with a peak current emerged at -1.01 V (vs Ag/AgCl) representing the occurrence of CO2 reduction reaction. In addition, the mechanism of PEC was proposed for the photocathode where the necessity of a bias potential in the range of 0.27 to -1.0 V vs Ag/AgCl was identified which could effectively inhibit the electron-hole (e-/h+) recombination process leading to an enhancement of CO2 reduction reactions.